Genetic diversity between Malvi and Nimari breeds of zebu cattle using RAPD markers - PARMAR, S N S; YADAV, B R; SRIVASTAVA, P N (The Indian Journal of Animal Sciences, 2014)
The present study investigated the lise of the random amplified polymorphic DNA (RAPD) method to detect genctic variation in Malvi and Nimuri callie of Madhya Pradesh. The blood samples for the present study were collected from 33 Malvi and 39 Nimari animals from Government Malvi Cattlc Breeding Farm, Agar, Malwa, Distt. Shajapur and Government Cattle Brecding Farm, Rodia, Distt. Khargone of Madhya, Pradesh respectively. The short arbitral)' oligonucleotide primers with high G-C content were employcd on a PCR programme, initial denaturation (94°C2 min) followed by 40 cycles of denaturation (94°C/min), annealing (36°C/1 min), and linal extension at 72°c for 5 min. Only distinet and prominenl bands were scored. Band sharing values within the Malvi animals ranged from 0.40 to 0.88, whereas in Nimari animals the values varied from 0.70 to U.9S. The combined dendograrn constructed for both the breeds, based on Jaccard's clusters separating the Malvi and Nunari animals as 2 different breeds.